Perceived Social Support from Classmates in Selected Roles related to Bullying - Kressa, Jiří (e-Pedagogium, 2018)
The paper presents partial conclusions from the research carried out by researchers at the Psychological Institute of AS and the Pedagogical Faculty of USB. The research focuses on social support from classmates at elementary schools as perceived by pupils in certain roles related to bullying. The roles related to bullying were identified and empirically verified by C. Salmivalli with her co-workers (1996). The research investigates male and female pupils aged 11-13 in three identified roles - the bully, the bullied pupil, and his/her advocate/defender of bullying. Social support is important for every person, and perceived social support is a significant indicator of its quality. The results highlight differences in the perception of support from classmates among the different roles described, especially the higher rate of perceived support in advocates of the bullied ones.
Keywords: social support; bullying; defenders of bullying